The Exploring the Use of ChatGPT on EFL Students' Writing Anxiety at Mulawarman University - misel misi; Desy Rusmawaty; Ichi Ahada; Widia Anggraeny Suharno (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2026)
This study aims to identify the writing anxiety levels, to explore students experiences the use of ChatGPT in supporting their writing and to examine students’ perceptions of the role ChatGPT in reducing writing anxiety at Mulawarman University. This research employed a qualitative case study design involving six final-year students selected through purposive sampling. Data were collected using a questionnaire (SLWAI) by Cheng 2004 and semi-structured interviews, then analyzed using thematic analysis. Thematic analysis of the interview data identified three major themes: The analysis generated three major themes: students’ writing anxiety levels, students’ experiences using ChatGPT in supporting writing, and ChatGPT’s role in reducing writing anxiety. The findings revealed that the majority of students experienced high levels of writing anxiety (69.2%), followed by moderate (25.6%) and low anxiety (6.4%), indicating that writing in English remains a significant challenge. In terms of learning experiences, students reported using ChatGPT for brainstorming ideas, correcting grammar, enhancing vocabulary, and receiving immediate feedback on their writing. Furthermore, ChatGPT was perceived as an effective tool in reducing writing anxiety by lowering students’ fear of making mistakes, increasing their confidence, and improving their motivation to complete writing tasks.These findings suggest that ChatGPT not only functions as a writing support tool but also serves as a psychological aid that helps students manage anxiety and engage more actively in the writing process. Keywords: Writing Anxiety, ChatGPT, EFL Students.